2012
DOI: 10.1210/jc.2011-2107
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Calcification in Mild Primary Hyperparathyroidism

Abstract: Mild PHPT is associated with subclinical aortic valve calcification. PTH, but not serum calcium concentration, predicted aortic valve calcification. PTH was a more important predictor of aortic valve calcification than well-accepted cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Indeed, valvular and annular calcification exhibit histopathologic features of bone formation and remodeling. (7–9) and have been linked to Vitamin D receptor polymorphisms,(36) parathyroid gene variants,(37) hyperparathyroidism,(38) and serum phosphate levels. (39) Furthermore, inflammation may link the pathophysiology of the skeletal and cardiovascular systems, as pro-inflammatory cytokines acting to promote bone resorption instead act to activate osteogenic programs in vascular and valvular smooth muscle cells and myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, valvular and annular calcification exhibit histopathologic features of bone formation and remodeling. (7–9) and have been linked to Vitamin D receptor polymorphisms,(36) parathyroid gene variants,(37) hyperparathyroidism,(38) and serum phosphate levels. (39) Furthermore, inflammation may link the pathophysiology of the skeletal and cardiovascular systems, as pro-inflammatory cytokines acting to promote bone resorption instead act to activate osteogenic programs in vascular and valvular smooth muscle cells and myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…PHPT appears to be associated with an increased risk of developing left ventricular hypertrophy, impaired diastolic filling, and myocardial calcification [4244]. Yu et al [45] observed in a retrospective population-based study in Tayside, Scotland, that mild PHPT (calcium <2.9 mmol/L) also was associated with an increased risk of cardiovascular and cerebrovascular disease in comparison to the age- and sex-matched general population and that this increase in mortality was similar to those with symptomatic or severe disease.…”
Section: Presentationmentioning
confidence: 99%
“…Interestingly, the only paper published after 2008 on this topic showed that in mild PHPT, aortic calcification was predicted by PTH and not by calcium levels, after corrections for well-known cardiovascular risk factors (88). So far, there are no studies in NC-PHPT regarding structural heart involvement.…”
Section: Structural Heart Involvementmentioning
confidence: 99%